Analisis Pembiayaan Qardhul Hasan Dalam Pengembangan Usaha Mikro Kecil Menengah Pada Bank Wakaf Mikro Pondok Pesantren As’ad - Nurul Prastio; Hansen Rusliani; Nurfitri Martalia (Komunitas Dosen Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are industries that are capable of helping the development of the Indonesian economy. However, there are internal challenges for MSMEs, namely capital problems, sharia-based banking emerges as a capital solution that avoids usury, one of which is Qardhul Hasan financing where this contract is a loan contract for goods or assets without compensation, aiming to take advantage of the goods or assets lent . The Islamic financial institution in Jambi Province that provides this contract is the As'ad Islamic Boarding School Micro Waqf Bank, this contract aims to be used as business capital in order to develop micro businesses owned by customers. Research objective: To find out how to finance Qardhul Hasan in the development of MSMEs at the As'ad Islamic Boarding School Micro Waqf Bank. Research theory: According to Muhammad in the Islamic Bank Management Book, financing is explained as funding issued to support planned investments, either carried out alone or carried out by other people. This study used qualitative research methods. Data collection techniques using interviews, observation and documentation. Research results: BWM Pondok Pesantren As'ad distributes Qardhul Hasan financing using sharia principles without collateral and interest. The increase in the amount of production and total income of customers has encouraged economic development around the As'ad Islamic Boarding School. There are obstacles in the installment payment process, namely some customers are not present. The solution that has been made by the bank and customers is to change the time and representatives of each member or bank employee who are not present.